MONITORING KEANEKARAGAMAN JENIS BURUNG PADA BERBAGAI TUTUPAN LAHAN DI CIBINONG SCIENCE CENTER (CSC), JAWA BARAT - Yohanna Dalimunthe (BERITA BIOLOGI, 2020)
Birds play an essential role in ecosystems, especially in urban landscapes such as the Cibinong Science Center (CSC). As an urban landscape, CSC always experiences land cover changes due to the development of research infrastructure resulting in various human-made land cover types. This study aims to determine the diversity of birds in various types of land cover as a community response to CSC development dynamics. Bird data was collected using the point count method modified with a grid (plot) measuring 200mx200m with a radius of observation as far as 50m at 34 points. Landsat images were analyzed from 2006 to 2018 to see changes in land cover changes. The observations show that there are 35 species of birds. Among those, three birds are protected by Indonesian regulation. There are six type of land cover in CSC paddy fields, buildings, opened area, farm land, plantation, and water. CSC has total diversity S(mean) = 32 covering 65% of all recorded birds. At land cover level, building area show the highest diversity (Shannon=2.03) while paddy fields is the lowest (Shannon=1.45). Based on the Landsat imagery, there are several changes in vegetation and the addition of some buildings.